The Effect of Celebrity Endorser, Brand Image, and Product Quality on The Purchase Decision of Sariayu Martha Tilaar Cosmetics - Iin Aulia Fitri; Rahmad Wijaya; Dewi Nurjannah (Universitas Muhammadiyah Malang, 2022)
This research aims to prove empirically the effect of a celebrity endorser, brand image, and product quality on the purchasing decision of Sariayu Martha Tilaar in Malang. The independent variables in this research are celebrity endorsers, brand image, and product quality. The dependent variable is the purchase decision. The sample size was 100 people with non-probability sampling. Data collection technology is this study used by questionnaire. Data analysis technique using multiple linear regression. The results of the study indicate that the celebrity endorser variable has an effect on purchasing decisions, brand image affects purchasing decisions, and product quality affects purchasing decisions.